Identification and Classification of Anthropogenic Landform in Parangtritis Hills Landscape - Dwi Putra, Boma Karunia; Setiawan, Muhammad Anggri; Mutaqin, Bachtiar Wahyu (Universitas Veteran Bangun Nusantara, 2024)
Human activities alter the Earth's morphology into anthropogenic landforms, both in urban and rural areas, including Desa Parangtritis. These interventions create new characteristics in the landscape, such as pseudourban formations on plains and morphological changes in hills, posing environmental risks if not managed properly. This study uses a comparative descriptive spatial analysis method, comparing variations between anthropogenic and natural landforms. Digital Elevation Model (DEM) data and orthophoto were utilized to delineate and identify anthropogenic landforms. The results indicate that the hillsides in Desa Parangtritis are divided into structural and solutional landforms, each with varying levels of human intervention. The solutional landform falls under a